THE ROLE AND STRATEGY OF THE ASSOCIATION OF SOUTHEAST ASIAN NATIONS (ASEAN) IN PROTECTING MIGRANT FISHERS IN SOUTHEAST ASIA AGAINST MODERN SLAVERY - Belardo Prasetya Mega Jaya; Muhammad Rusli Arafat; Asep Hakim Zakiran; Mohd Hazmi Mohd Rusli; Fareed Mohd Hassan; Noor Dzuhaidah Osman; Amalina Ahmad Tajudin (Malaysian Journal of Syariah and Law)
The issue of contemporary slavery within the fishing sector has afflicted the region for decades. The situation is difficult due to the cross-territorial jurisdiction of other nations. Nonetheless, this has not been regarded with due seriousness at the regional level, particularly by the Association of Southeast Asian Nations (ASEAN). This research intends to examine the role and strategy of the Association of Southeast Asian Nations (ASEAN) in safeguarding migrant fishers in Southeast Asia against modern slavery. This research employed normative legal analysis. The contribution of this research lies in the authors’ recommendations for policy reforms within ASEAN aimed at enhancing the protection of migrant fishermen in Southeast Asia from modern slavery, along with the proposal of innovative strategies to effectively address this issue. The research indicated that ASEAN played multiple roles in establishing legislation and enabling ASEAN agencies to safeguard migrant fishers in Southeast Asia against modern slavery. The authors’ analysis indicate that ASEAN requires reforms in order to further enhance the protection of migrant fishers in Southeast Asia from modern slavery. To this end, ASEAN needs effective and comprehensive measures to address this issue. These may include enhancing its recruitment systems and migrant fishers’ contracts, providing training and certification for migrant fishers, implementing proper supervision in recruitment processes, drafting clear employment agreements and regulations for working at sea, and establishing complaints mechanisms to ensure equality and fair opportunities for migrant fishers. These efforts can be achieved, inter alia, by collaborating with ASEAN Member States and relevant stakeholders, ratifying the ILO Convention C-188 and other related agreements, and re-evaluating the interpretation of the ASEAN Way in relation to migrant fishers. Key areas of focus should include: recruitment systems and migrant fishers’ contracts; training and certification for migrant fishers; implementation of supervision and complaints mechanisms; collaboration with Member States and stakeholders; ratification of ILO C-188 and related agreements; and reevaluation of the ASEAN Way’s interpretation.